A Wireless Greenhouse Monitoring System Based on Solar Energy - Liai Gao; Man Cheng; Juan Tang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
To resolve the problems of complicated cabling and costly wired network in the current system, we designed a wireless greenhouse monitoring system based on ZigBee and GSM technology.  The system consists of two parts: a wireless sensor network and remote control terminal. According to parameters distribution in the monitoring regional, a wireless transmission network was formed, all of the node in the network using solar power. In the remote control terminal, the study developed a simplified expert decision system, in which the part of greenhouse control decision adopts the fuzzy decoupling control algorithm to realize the temperature and humidity decoupling control and increase the accuracy of decision-making.According to the experimental test, the monitoring system can run well under the conditions in northern China greenhouses. It can realize real-time, accurate monitoring and collecting of parameters data in the greenhouse environment; the remote control terminal can give effective decision management solutions. Our future work will mainly be solar photovoltaic panel servo system and image transmission. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3305